2018
DOI: 10.1002/pbc.26964
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and management of ganglioneuroma and ganglioneuroblastoma‐intermixed in children and adolescents

Abstract: GN and GNB-I have a slow growth rate and resection can be associated with significant morbidity. Watch and wait approaches should be considered for some GN and GNB-I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 33 publications
(71 reference statements)
0
32
1
2
Order By: Relevance
“…Adult GNB tumors >8 cm in diameter arising from the retrospective cavity tend to metastasize to other distant organs . The size of the lesion in the present case (13 cm) was large compared to those in other reports of mediastinal GNB, and therefore the risk of recurrence in our case may have been increased at the time of diagnosis. Therefore, cases of adolescent/adult GNB should be followed‐up carefully even after complete resection.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…Adult GNB tumors >8 cm in diameter arising from the retrospective cavity tend to metastasize to other distant organs . The size of the lesion in the present case (13 cm) was large compared to those in other reports of mediastinal GNB, and therefore the risk of recurrence in our case may have been increased at the time of diagnosis. Therefore, cases of adolescent/adult GNB should be followed‐up carefully even after complete resection.…”
Section: Discussioncontrasting
confidence: 43%
“…Here, we present the clinical course of mediastinal GNB discovered in a 17‐year‐old male adolescent. As GNBs occur almost exclusively in the pediatric population, adult onset GNB is uncommon and the mediastinum as the primary site is a further rare clinical manifestation . These points are noteworthy in the present case.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The pathogenesis of GN is still unclear. Most GNs are primary, but it has been reported that some GNs also arise after treatment for neuroblastoma or as a result of spontaneous neuroblastoma differentiation (10). GNs, just like PCCs, originate from neural crest cells in the neuroectoderm.…”
Section: Discussionmentioning
confidence: 99%